Prooxidant Effects of Verbascoside, a Bioactive Compound from Olive Oil Mill Wastewater, on In Vitro Developmental Potential of Ovine Prepubertal Oocytes and Bioenergetic/Oxidative Stress Parameters of Fresh and Vitrified Oocytes. (25th February 2014) - Dell'Aquila, M. E.; Bogliolo, L.; Russo, R.; Martino, N. A.; Filioli Uranio, M.; Ariu, F.; Amati, F.; Sardanelli, A. M.; Linsalata, V.; Ferruzzi, M. G.; Cardinali, A.; Minervini, F.
Abstract : Verbascoside (VB) is a bioactive polyphenol from olive oil mill wastewater with known antioxidant activity. Oxidative stress is an emerging problem in assisted reproductive technology (ART). Juvenile ART is a promising topic because, in farm animals, it reduces the generation gap and, in human reproductive medicine, it helps to overcome premature ovarian failure. The aim of this study was to test the effects of VB on the developmental competence of ovine prepubertal oocytes and the bioenergetic/oxidative stress status of fresh and vitrified oocytes. In fresh oocytes, VB exerted prooxidant short-term effects, that is, catalase activity increase and uncoupled increases of mitochondria and reactive oxygen species (ROS) fluorescence signals, and long-term effects, that is, reduced blastocyst formation rate. In vitrified oocytes, VB increased ROS levels. Prooxidant VB effects in ovine prepubertal oocytes could be related to higher VB accumulation, which was found as almost one thousand times higher than that reported in other cell systems in previous studies. Also, long exposure times of oocytes to VB, throughout the duration of in vitro maturation culture, may have contributed to significant increase of oocyte oxidation. Further studies are needed to identify lower concentrations and/or shorter exposure times to figure out VB antioxidant effects in juvenile ARTs.